Time trends incidence of celiac disease in a Spanish population. - Julia María Cabo Del Riego; María Jesús Núñez-Iglesias; Andrés Blanco Hortas; Tamara Álvarez Fernández; Ignacio Corchero; Silvia Novío; José Paz Carreira; Carmen García-Plata González; José Abel González-Ramirez; Sofia Zaera; Manuel Freire-Garabal Núñez (PLoS ONE)
Background/objective Very few studies on celiac disease (CD) incidence across all age groups have been carried out so far, particularly in Spain. We evaluate the time trend incidence of CD of children, adults and elderly. Methods Prospective study. Using an integrative primary and tertiary care setting approach with a standardized algorithm we identify all new cases of CD from January 1, 2012, to December 31, 2019, in a well-defined area of Galicia county, Spain. The crude incidence rate of CD was calculated as new cases per 100.000 person/year. Incidence rates were stablished by age categories 0-4, 5-19, 20-44, 45-64, 65-84, ≥ 85 and periods of 1-year intervals. Results Between 2012 and 2019, 19,564 patients with suspicion and risk of CD were tested. 294 new cases of CD were diagnosed. Increasing CD incidence was observed from 13.11 per 100.000 person/year in 2012 to 20.92 per 100.000 100.000 person/year in 2019 (95% CI = 6.8-15.5). The temporal trend in incidence rates diverges between different age groups; showing a high incidence with stable pattern in children and young people whereas exhibiting an increasing incidence in adult/elderly, so that the incidence almost triple from 2012 to 2019. Classic CD symptoms decreasing frequency among incident cases was observed over time. Conclusions A standardized algorithm for CD diagnosis with first-line serology testing followed by biopsy, if needed according to guidelines, confirmed the CD increasing incidence over 8 years period.